2014
DOI: 10.3329/ijarit.v4i1.21088
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of some chili (Capsicum annuum L.) genotypes

Abstract: A study on genetic diversity was conducted with 54 Chili (Capsicum annuum L.) genotypes through Mohalanobis's D 2 and principal component analysis for twelve quantitative characters viz. plant height, number of secondary branch/plant, canopy breadth , days to first flowering, days to 50% flowering, fruits/plant, 5 fruits weight, fruit length, fruit diameter, seeds/fruit, 1000 seed weight and yield/plant were taken into consideration. Cluster analysis was used for grouping of 54 chili genotypes and the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 5 publications
7
16
0
3
Order By: Relevance
“…Therefore, highly divergent genotypes would produce a broad spectrum of segregation in the subsequent generations enabling further selection and improvement and it is important for pepper breeding program. Such recommendations were also made by Nsabiyera et al 2013, Hasan et al (2014), Hassan et al (2015), Janaki et al (2016), Razzaq et al (2016) and Pujar et al (2017), in which the greater the distance between clusters, the wider the genetic diversity would be between the genotypes.…”
Section: Estimation Of Inter Cluster Square Distances (D 2 )mentioning
confidence: 92%
“…Therefore, highly divergent genotypes would produce a broad spectrum of segregation in the subsequent generations enabling further selection and improvement and it is important for pepper breeding program. Such recommendations were also made by Nsabiyera et al 2013, Hasan et al (2014), Hassan et al (2015), Janaki et al (2016), Razzaq et al (2016) and Pujar et al (2017), in which the greater the distance between clusters, the wider the genetic diversity would be between the genotypes.…”
Section: Estimation Of Inter Cluster Square Distances (D 2 )mentioning
confidence: 92%
“…The various traits explained by PC1 and PC2 was capable of resolving the genotypes to their respective species level. Cluster analysis and principal component analysis were used to group 54 chilli genotypes (Capsicum annuum L.) into seven clusters [3]. Based on mean, variance and group distance, in his study, clusters I and III along with other clusters were suggested for hybridization programme.…”
Section: Plate 3 Flower Fruit and Leaf Types Of Some Genotypes In Dmentioning
confidence: 99%
“…The origin of this spice and vegetable crop can be traced to South and Central America [2]. Green fruits of chilli are used as vegetable whereas ripe dried fruits as a spice because of its pungency and pleasant flavour [3]. Mature fruits of chilli contain carotenoid pigments, flavonoids and significant amounts of vitamin C, B1 and B2.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the chill varieties are local cultivars or landraces. Landraces are variable plant populations adapted to local agro climatic conditions, which are locally named, selected and maintained by the traditional farmers to meet their social, economic, cultural and ecological needs (Hasan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%